1976
DOI: 10.1111/j.1348-0421.1976.tb00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Streptococcus mutans among Japanese Children

Abstract: An epidemiological investigation was carried out to identify and determine the serotypes of Streptococcus mutans from carious lesions of young Japanese children. For this purpose, a direct fluorescent antibody technique was mainly used. Fluorescein isothiocyanate-conjugated antibodies were prepared for the five known serotypes of S. mutans. Cross reactions and nonspecific reactions were eliminated by adsorption, counterstaining, or DEAE-cellulose column chromatography.Agar-gel immunodiffusion was used to disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
6
1
Order By: Relevance
“…Most of the studies, however, have reported the occurrence of serotype e with highest prevalence that ranged from 2% to 30% followed by serotypes: f and k in the range of 1-25% and around 5% respectively [Table 2]. [171819202122232425262728] Since the findings of our study are in contrary to those that have been observed earlier, we speculate that this could be due to a shift in S. mutans serotype in subjects from this region. Such serotype shifts have been reported elsewhere in other strains such as Streptoccocus agalactiae from Group B Streptococcus for example, where in S. agalactiae serotype Ia was found to occur consistently with a higher prevalence in North American population relative to those from other geographic regions ( P < 0.005).…”
Section: Discussioncontrasting
confidence: 93%
“…Most of the studies, however, have reported the occurrence of serotype e with highest prevalence that ranged from 2% to 30% followed by serotypes: f and k in the range of 1-25% and around 5% respectively [Table 2]. [171819202122232425262728] Since the findings of our study are in contrary to those that have been observed earlier, we speculate that this could be due to a shift in S. mutans serotype in subjects from this region. Such serotype shifts have been reported elsewhere in other strains such as Streptoccocus agalactiae from Group B Streptococcus for example, where in S. agalactiae serotype Ia was found to occur consistently with a higher prevalence in North American population relative to those from other geographic regions ( P < 0.005).…”
Section: Discussioncontrasting
confidence: 93%
“…All the root caries plaque and dentin samples contained mutans streptococci, irrespective of the caries activity. The distribution of serotypes was reflected in saliva and confirmed that S. mutans (serotypes c, e, and f) may be isolated more frequently from active caries lesions than S. sobrinus (serotypes d and g) (19,33,42). Two individuals were colonized by at least three different serotypes on the same root surface.…”
Section: Discussionmentioning
confidence: 63%
“…These studies confirmed the relationship between the prevalence of S. mutans in the plaque and the development of caries. The isolated S. mutans strains all belonged to serotype c/e/f, whieh was found to be the most common serotype group in many studies (5,10,19,20).…”
Section: Discussionmentioning
confidence: 97%